Religious Tourism In The Tourism System - Mojshevich Eidelman, Boris; Kazan Federal University, Institute of Management, Economics and Finance (2017)
The paper considers the concept of religious tourism. Religious tourism is the departure of a person from a country of residence for a period of no more than six months in order to visit holy places and centers of religion. On the other hand, this concept can be viewed as an activity aimed at providing services to the tourists travelling for religious purposes. One distinguishes the pilgrimage tourism and the religious tourism of excursion - cognitive focus. The difference between these two types is that the religious tourism of excursion - cognitive focus means visiting temples and holy places without the tourists’ participation in the religious life of the shrine. The Pilgrimage tourism provides an opportunity to participate in worshipping and praying. The Pilgrimage can also be classified according to the number of participants, i.e. individual, family, group. If one considers the duration of the tour, one can identify long and short pilgrimages. Depending on the location of the shrine, there are domestic and foreign tours